Membrane domains and flagellar pocket boundaries are influenced by the cytoskeleton in African trypanosomes. - Gadelha, C; Rothery, S; Morphew, M; McIntosh, JR; Severs, N; Gull, K (2009)
A key feature of immune evasion for African trypanosomes is the functional specialization of their surface membrane in an invagination known as the flagellar pocket (FP), the cell's sole site of endocytosis and exocytosis. The FP membrane is biochemically distinct yet continuous with those of the cell body and the flagellum. The structural features maintaining this individuality are not known, and we lack a clear understanding of how extracellular components gain access to the FP. Here, we have defined domains and boundaries on these surface membranes and identified their association with internal cytoskeletal features. The FP membrane appears largely homogeneous and uniformly involved in endocytosis. However, when endocytosis is blocked, receptor-mediated and fluid-phase endocytic markers accumulate specifically on membrane associated with four specialized microtubules in the FP region. These microtubules traverse a distinct boundary and associate with a channel that connects the FP lumen to the extracellular space, suggesting that the channel is the major transport route into the FP.